Role of Xpert MTB/RIF in differentiating tuberculosis from sarcoidosis in patients with mediastinal lymphadenopathy undergoing EBUS-TBNA: a study of 147 patients - Dhooria, Sahajal; Gupta, Nalini; Bal, Amanjit; Sehgal, Inderpaul Singh; Aggarwal, Ashutosh Nath; Sethi, Sunil; Behera, Digambar; Agarwal, Ritesh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: In patients with intrathoracic lymphadenopathy, differentiating tuberculosis from sarcoidosis is often difficult. We hypothesized that Xpert MTB/RIF assay, a semi-automated hemi-nested PCR would help in this regard. Objective: To evaluate the performance of Xpert MTB/RIF in the differential diagnosis of tuberculosis and sarcoidosis. Methods: This was a retrospective analysis of patients with intrathoracic lymphadenopathy who underwent endobronchial ultrasound (EBUS)-guided transbronchial needle aspiration (TBNA), and were diagnosed as either tuberculosis or sarcoidosis. The results of Xpert MTB/RIF assay, tuberculin skin test and endosonographic characteristics (heterogeneous echotexture and coagulation necrosis sign) of the lymph nodes were compared between the two groups. Results: During the study period, 465 EBUS procedures were performed and a diagnosis of sarcoidosis (n=94) or tuberculosis (n=53) was made in 147 patients. Xpert MTB/RIF was positive in 26 (49.1%) and two (2.1%) patients with tuberculosis and sarcoidosis, respectively. The sensitivity, specificity, positive and negative predictive values of Xpert MTB/RIF in the diagnosis of tuberculosis were 49.1 %, 97.9%, 92.9% and 77.3%, respectively. The presence of any of the four features namely positive Xpert MTB/RIF, positive tuberculin skin test, heterogeneous echotexture of the lymph nodes, or the presence of endosonographic coagulation necrosis sign yielded a sensitivity and negative predictive value of 83.0% and 88.0%, respectively in the diagnosis of tuberculosis versus sarcoidosis. Conclusions: Xpert MTB/RIF has good specificity and positive predictive value in the diagnosis of tuberculosis, and is a useful investigation in separating tuberculosis from sarcoidosis.